1992
DOI: 10.1063/1.463622
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative excitation of CF4, CCl4, and chlorofluoromethanes by collisions with argon and helium active species

Abstract: Dissociative excitation of CFnCl4–n (n=0–4) by collisions with Ar and He active species has been studied by observing uv and visible emissions in the Ar and He afterglows. Emissions from such excited fragments as Cl*, Cl*2, CF*, CCl*, CCl+*, ArCl*, CF*2, CCl*2, CFCl*, and CF*3 were observed. New continuous bands which may be related to Cl*2, CFCl*, CCl*n(n=2,3), and CCl+*n(n=2,3) were found in the reactions of CFCl3 and CCl4. The effects of ion trapping and SF6 addition into the discharge flow indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…The excitation sources employed have been an ArF laser operating in the multi-photon mode, 2 high energy electrons, [3][4][5][6][7][8][9][10][11][12] fixedenergy gaseous lamps, 13 microwave discharges 14 and rare gas metastables. 15 Despite the many advantages of using tunable VUV photons from a synchrotron radiation (SR) source for such studies, 1 only one such study, on CF 2 Cl 2 , has been reported. 16 For the work presented here, SR from both the Daresbury Laboratory, UK and BESSY1, Germany sources is used to perform complimentary fluorescence experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The excitation sources employed have been an ArF laser operating in the multi-photon mode, 2 high energy electrons, [3][4][5][6][7][8][9][10][11][12] fixedenergy gaseous lamps, 13 microwave discharges 14 and rare gas metastables. 15 Despite the many advantages of using tunable VUV photons from a synchrotron radiation (SR) source for such studies, 1 only one such study, on CF 2 Cl 2 , has been reported. 16 For the work presented here, SR from both the Daresbury Laboratory, UK and BESSY1, Germany sources is used to perform complimentary fluorescence experiments.…”
Section: Introductionmentioning
confidence: 99%
“…At the relatively small partial argon pressure р(Ar) = 5-10 kPa, the 175 nm ArCl (В → Х) and 258 nm Cl 2 (D ' → A') bands in the emission spectrum were of comparable intensities. Emission of the bands of the argon chlo ride molecule λ = 169 nm ArCl (D → X) and 199 nm ArCl (C → A) [12,13], which were revealed only at the lowered pressure of the working mixture, were less intense. With the increase in the partial argon pres sures (р > 20-30 kPa) and freon vapors (to 200-300 Pa), the intensity of the emission band λ = 258 nm Cl 2 (D' → A') began to prevail over the intensity of the argon chloride band.…”
Section: Experimental Techniquementioning
confidence: 94%
“…Such types of resource characteristics of the lamp shows that the CCl 4 molecules do not partici pate directly in the formation of ArCl* (B) and (D') molecules, and the products of the decay of freon mol ecules in the barrier discharge are the main ones in the process of the formation of these particles. The con stant of the direct reaction rate of the formation of ArCl molecules (B, С) in the process of the collision between Ar( 3 P 2 ) atoms and the CCl 4 molecule of 1.6 × 10 -11 cm 3 s -1 is given in [13]. This is a quite small value; therefore, the ArCl molecules (B; C) should be formed more effectively in "harpoon" reactions of Ar( 3 P 2 ) atoms with uncharged products (radicals), the product of the decay of the CCl 4 molecule and in reactions of the ion-ion recombination of positive Ar + , ions with the negative Clion.…”
Section: Experimental Techniquementioning
confidence: 99%
See 2 more Smart Citations